Penerapan inovasi dan teknologi pengolahan batang sawit untuk varian produk mebel dan interior bangunan di Desa Pancuran Gading, Kecamatan Tapung, Kampar - Fakhri Fakhri; Alfian Malik; Elianora Elianora; Zulkifli Nurdin; Pedia Aldy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Solid waste from oil palm trunks after replanting activities in oil palm plantations has the potential to be utilized. However, the community's perspective considers that oil palm trunks cannot be utilized because they are easy to mold and have low strength. The application of innovation and technology will be able to provide solutions to community empowerment and utilization of the potential of oil palm trunks. The purpose of the service activity is to provide assistance to innovation and technology on how to use palm oil trunk waste as raw material for furniture and building interior products in Pancurangading Village, Tapung District, Kampar Regency. The results of service activities can be declared successful in providing community understanding, attitudes, and skills. The success rate of the program based on pre-test and post-test data was 37.5% (do not understand) and increased to 84.7% (understand). People's perceptions of oil palm trunks have been able to change so that they are able to understand, utilize and produce palm wood raw materials into various variants of furniture and building interiors. Utilization of oil palm trunks can provide business opportunities for the community in the future.